Africa's Silk Road : China and India's New Economic Frontier - Broadman, Harry G. (Washington, DC World Bank, 2007)
As illustrated in Africa's Silk Road: China and India's New Economic Frontier, the new South-South economic relations present real opportunities-as well as challenges-to African countries. They also highlight the need for complementary reforms by China and India to support more vigorous African development. In analyzing Africa's intensifying relationships with China and India, Africa's Silk Road examines the trends to date and considers the implications of these developments for the economic future of the African continent. The diagnosis cautions that the opportunities engendered by China and India's trade and investment with Africa will not necessarily be converted into growth and poverty reduction in the region. A critical finding of the study is that it is not just the quantity of these trade and investment flows that matters-it is also the quality of the overall commercial relationships underlying as well as shaping these flows. This paper contains the following headings: connecting two continents; performance and patterns of African-Asian trade and investment flows; challenges at the border - Africa and Asia's trade and investment policies; behind-the-border constraints on African-Asian trade and investment flows; between-the-border factors in African-Asian trade and investment; and investment-trade linkages in African-Asian commerce - scale, integration, and production networks.
Include Index, Bibliography and Table
Keywords: China -- India -- Africa